Utilizing Pipeline Quality and Facility Sustainability to Optimize Crude Oil Supply Chains - Billy Gray; Erick C. Jones; Yvette Weatherton; Restu Sunarto-Bussey; Harrison Armstrong (International Journal of Supply Chain Management, 2013)
In this paper, the distribution center (DC) model shown in Shapiros Modeling the Supply Chain is modified to show optimal locations to place small and large refineries based on transportation distances, refinery building costs, and the costs associated with refinery sustainability and pipeline quality. Though this model was originally used to determine the optimal locations to place distribution centers based on transportation distances and the size of the distribution centers, this model was modified to allow the use of different costs associated with the quality condition of the pipeline and the costs of sustaining an environmentally friendly facility. The case used to prove the model is the Indonesian oil industry due to how an increase in efficiency and excess capacity could provide another viable country to supply oil to the United States. The outputs of this paper are efficiency frontiers that show how the costs of pipeline quality and facility sustainability affect the overall costs of the Indonesian oil industry and a model that can be used to evaluate the oil industries in other countries.